2021
DOI: 10.1098/rsos.211168
|View full text |Cite
|
Sign up to set email alerts
|

The Grotthuss mechanism for bifunctional proton transfer in poly(benzimidazole)

Abstract: Poly(benzimidazole) (PBI) has received considerable attention as an effective high-temperature polymer electrolyte membrane for fuel cells. In this work, the Grotthuss mechanism for bifunctional proton transfer in PBI membranes was studied using density functional theory and transition state theory. This study focused on the reaction paths and kinetics for bifunctional proton transfer scenarios in neutral ([PBI] 2 ), single (H + [PBI] 2 ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“….60 Â 10 À14 s À1 , whereas for the same reaction at 3 ¼ 1 (Int2b / TS3 / Int3), k S-Wig f ¼ 1.71 Â 10 8 s À1 , which indicates that acid catalyst (1) (III) is kinetically favorable in a low local dielectric environment. This is in accordance with our previous work, 11,14,24 in which the uctuation of the local dielectric environment was conrmed to govern the kinetics of proton transfer processes; based on this analysis, React / TS1 / Int1 (1,3-dipolar cycloaddition (I)) is kinetically more favorable than React 3 / TS1 3 / Int1 3 (k S-Wig f ¼ 3.44 Â 10 3 and k S-Wig,3 f ¼ 2.44 Â 10 3 s À1 , respectively). Attempt was made to correlate the rate constants obtained from the TST method with the experimental data.…”
Section: Kinetics and Thermodynamics Of The Elementary Reactionssupporting
confidence: 94%
See 4 more Smart Citations
“….60 Â 10 À14 s À1 , whereas for the same reaction at 3 ¼ 1 (Int2b / TS3 / Int3), k S-Wig f ¼ 1.71 Â 10 8 s À1 , which indicates that acid catalyst (1) (III) is kinetically favorable in a low local dielectric environment. This is in accordance with our previous work, 11,14,24 in which the uctuation of the local dielectric environment was conrmed to govern the kinetics of proton transfer processes; based on this analysis, React / TS1 / Int1 (1,3-dipolar cycloaddition (I)) is kinetically more favorable than React 3 / TS1 3 / Int1 3 (k S-Wig f ¼ 3.44 Â 10 3 and k S-Wig,3 f ¼ 2.44 Â 10 3 s À1 , respectively). Attempt was made to correlate the rate constants obtained from the TST method with the experimental data.…”
Section: Kinetics and Thermodynamics Of The Elementary Reactionssupporting
confidence: 94%
“…Because the FDC1 enzyme is exceedingly large for high-level ab initio methods and because our previous studies showed that the mechanisms for proton transfer in heterocyclic aromatic systems can be studied reasonably well using the B3LYP method with the DZP basis set, [11][12][13] the B3LYP/DZP method was used in this study; our benchmark calculations on bifunctional proton transfers in poly(benzimidazole) (PBI) H-bond systems 14 conrmed that the B3LYP/DZP method yields approximately the same equilibrium and transition structures and relative interaction energies as the B3LYP/TZP method with reasonable computational resources. In this study, the model molecular clusters that were hypothesized in ref.…”
Section: Quantum Chemical Methodsmentioning
confidence: 99%
See 3 more Smart Citations